Time- and temperature-dependent mechanical and rheological behaviours of injection moulded biodegradable organoclay nanocomposites - Attila Bata; Péter Gerse; Emese Slezák; Ferenc Ronkay (Advanced Industrial and Engineering Polymer Research, 2024)
Injection moulded specimens were produced from biodegradable poly(butylene succinate) (PBS)/organomodified montmorillonite (OMMT) nanocomposites, after melt compounding in different compositions. WAXD studies demonstrated that the OMMT formed similar intercalation levels in the 2.5–10 w/w% additive ratio range. It was also proved by rotational rheometry that the nanoclay stacks form physical network above 5 w/w% concentration, which significantly influence the viscoelastic properties of the melt. The value of zero shear viscosity also changed accordingly, starting to increase above 5 w/w% nanoclay content. The OMMT content reduced the creep sensitivity measured in molten state.X-ray and DSC investigations showed that OMMT inhibits the crystallisation of PBS, resulting in a decrease in crystallinity at higher nanoclay ratios. As a result, the room temperature creep increased with the OMMT ratio.The Young's modulus linearly increases in the entire concentration range exceeding 1.2 GPa at 10 w/w% nanoclay content. The value of yield strength does not change significantly (35–40 MPa), but the strain at yield – which characterises stiffness – and the notched Izod impact strength already decrease at 2.5 w/w% OMMT content, but further increasing the nanoclay content has minor effect. However, the nanocomposite with 10 w/w% OMMT can be a real alternative to polypropylene (PP) and high-density polyethylene (HDPE) injection moulded products based on its mechanical properties.To characterise the effect of OMMT on dynamic mechanical properties, the S (Stiffening effectiveness), L (Loss effectiveness) and D (Damping effectiveness) indices were introduced to quantitatively describe the nanoclay effect intensity in each temperature range.